If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13.2 = 2pi * r Multiply ip * r 13.2 = 2ipr Solving 13.2 = 2ipr Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2ipr' to each side of the equation. 13.2 + -2ipr = 2ipr + -2ipr Combine like terms: 2ipr + -2ipr = 0 13.2 + -2ipr = 0 Add '-13.2' to each side of the equation. 13.2 + -13.2 + -2ipr = 0 + -13.2 Combine like terms: 13.2 + -13.2 = 0.0 0.0 + -2ipr = 0 + -13.2 -2ipr = 0 + -13.2 Combine like terms: 0 + -13.2 = -13.2 -2ipr = -13.2 Divide each side by '-2pr'. i = 6.6p-1r-1 Simplifying i = 6.6p-1r-1
| t^2-12t-28=0 | | 91+3b=37-3b | | 37-4x=77+6x | | x*x+x*y+x*y=0.64 | | |5x-1|/|x-2|=4 | | (4s+2)(5s^2+10s+3)= | | (0.7*1.5x)+(0.3*x)=4.5 | | 71+n=100 | | 3(2b+5a)= | | 3c+45=3-4c | | 1,3/16 | | (0.5*1.2x)+(0.5*x)=16 | | z^2-5=-7 | | z^2=-6 | | (0.5*1.2x)+(0.5*x)=8 | | (8)3/4×(4096)1/2÷1/(64)= | | 4y-5=7y-20 | | 13p+14q+p-6q-5p= | | X+3y+26whenx=2whatisy | | logb^8=-3 | | (0.61*1.2x)+(0.39*x)=6 | | 1120=(x+3)(x+4)(5+x)(6+x)(7+x) | | (3x^y^4-11xy^4)/55xy | | 23=m-19 | | 8x+18=3x-2 | | 12(x-3)-6=2(x+5)-2(2-4x) | | 24x+12y=60 | | X/2-17=9 | | (x^4)+(8x^3)+(20x^2)+(16x)+4=0 | | -7(x-4)+5(x+2)+2(2x-1)=0 | | -7x-22= | | 10+x=16x |